Cytochrome P450 2C19 loss-of-function polymorphism is a major determinant of clopidogrel responsiveness in healthy subjects - Hulot, Jean-Sébastien; Bura, Alessandra; Villard, Eric; Azizi, Michel; Remones, Véronique; Goyenvalle, Catherine; Aiach, Martine; Lechat, Philippe; Gaussem, Pascale (Blood, 2006)
The capacity of clopidogrel to inhibit ADP-induced platelet aggregation shows wide intersubject variability. To determine whether frequent functional variants of genes coding for candidate cytochrome P450 (CYP) isoenzymes involved in clopidogrel metabolic activation (CYP2C19*2, CYP2B6*5, CYP1A2*1F, and CYP3A5*3 variants) influence the platelet responsiveness to clopidogrel, we conducted a prospective pharmacogenetic study in 28 healthy white male volunteers treated for 7 days with clopidogrel 75 mg/d. We observed that pharmacodynamic response to clopidogrel was significantly associated with the CYP2C19 genotype. Twenty of the subjects were wild-type CYP2C19 (*1/*1) homozygotes, while the other 8 subjects were heterozygous for the loss-of-function polymorphism CYP2C19*2 (*1/*2). Baseline platelet activity was not influenced by the CYP2C19 genotype. In contrast, platelet aggregation in the presence of 10 μM ADP decreased gradually during treatment with clopidogrel 75 mg once daily in *1/*1 subjects, reaching 48.9% ± 14.9% on day 7 (P < .001 vs baseline), whereas it did not change in *1/*2 subjects (71.8% ± 14.6% on day 7, P = .22 vs baseline, and P < .003 vs *1/*1 subjects). Similar results were found with VASP phosphorylation. The CYP2C19*2 loss-of-function allele is associated with a marked decrease in platelet responsiveness to clopidogrel in young healthy male volunteers and may therefore be an important genetic contributor to clopidogrel resistance in the clinical setting.